2017
DOI: 10.5897/jeif2017.0875
|View full text |Cite
|
Sign up to set email alerts
|

Demand-driven determinants and self-reported barriers to financial inclusion in the West African Economic and Monetary Union (WAEMU)

Abstract: "Access to finance for all" has gained attention in the international development agenda in recent years. In the West African Economic and Monetary Union (WAEMU), the issue of financial inclusion is set at the level of priority but in several dimensions of financial inclusion, countries of the union lag behind the Sub-Saharan Africa and Asian benchmark countries. In this paper, factors that are important for financial inclusion in WAEMU are identified and it is investigated whether these factors are correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
1
0
1
Order By: Relevance
“…Thus, the lenient rules of documentation make the use of financial products much more manageable and frequent. This result is in line with the finding of numerous studies in the field such as Tomgouani (2017), Beck et al (2006), Shankar (2013), Razak et al (2017), Shihadeh (2018) and Kostov et al (2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, the lenient rules of documentation make the use of financial products much more manageable and frequent. This result is in line with the finding of numerous studies in the field such as Tomgouani (2017), Beck et al (2006), Shankar (2013), Razak et al (2017), Shihadeh (2018) and Kostov et al (2012).…”
Section: Discussionsupporting
confidence: 91%
“…This result disconfirms the hypothesis ( H3 ), and therefore, the hypothesis is not supported. This outcome is contrasting the results of some studies such as (Tomgouani, 2017; Demirgüç-Kunt et al , 2008; Ulwodi and Muriu, 2017; Razak et al , 2017; Kostov et al , 2012) who found that the distance from the house and the financial institution is the main factor that embeds the usage of financial services. This result can be interpreted as if the beneficiaries are interested in using the financial services provided; the distance does not matter.…”
Section: Discussioncontrasting
confidence: 70%